2009
DOI: 10.1111/j.1463-1318.2008.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology reporting in colorectal cancer: a proforma improves quality

Abstract: A template proforma and surgeon's contribution in relation to operative findings improves the quality of the histopathology report in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
(15 reference statements)
1
25
1
Order By: Relevance
“…The format of the histopathology report has traditionally been "free text." Quality studies have however shown that template (or synoptic) reporting is superior in ensuring that key parameters are reported [4][5][6][7][8][9]. Template reporting means that predefined standardized data elements are incorporated in the histopathology report.…”
Section: Introductionmentioning
confidence: 97%
“…The format of the histopathology report has traditionally been "free text." Quality studies have however shown that template (or synoptic) reporting is superior in ensuring that key parameters are reported [4][5][6][7][8][9]. Template reporting means that predefined standardized data elements are incorporated in the histopathology report.…”
Section: Introductionmentioning
confidence: 97%
“…20 Formal feedback from pathologists to surgeons regarding resection margins and planes of dissection is becoming the norm, 21 and quality of histopathological reports has been improved by introduction of a standardized pro-forma. 22 Clinical audit is well established as a professional requirement, 23 and anonymous reporting in many jurisdictions allows for open and transparent analysis of outcomes. 24 There is widespread awareness of the importance of opportunistic screening (colonoscopy 25 or CT colonography 26 ) resulting in diagnosis at far earlier disease stage.…”
mentioning
confidence: 99%
“…Although several studies have shown the positive effects of checklists or templates on the completeness of histopathology reports on colorectal carcinoma resections, [14][15][16][17][18][19][20][21][22][23] just one has included more specific data on the sustainability of template use. 18 In 2003-2006, the Cancer Registry of Norway and the Norwegian Society of Pathology collaborated on a project to develop structured electronic templates for histopathology reporting of cancer.…”
mentioning
confidence: 99%